2022
DOI: 10.1097/corr.0000000000002176
|View full text |Cite
|
Sign up to set email alerts
|

How Does Orthopaedic Surgeon Gender Representation Vary by Career Stage, Regional Distribution, and Practice Size? A Large-Database Medicare Study

Abstract: Background Orthopaedic surgery has the lowest proportion of women surgeons in practice of any specialty in the United States. Preliminary studies suggest that patients who are treated by physicians of the same race, ethnicity, cultural background, or gender feel more comfortable with their care and may have better outcomes. Therefore, understanding the discrepancies in the diversity of the orthopaedic surgeon workforce is crucial to addressing system-wide healthcare inequities. Questions/purposes (1) Does a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…35 Over the past two decades, the percentage of female orthopaedic residents has risen moderately from 11.0% in 2005 to 14% in 2017 (127.3% increase). 29,35,36 Interestingly, the field of musculoskeletal oncology is more representative of female surgeons (21.1%) than the orthopaedic workforce as a whole (5.0%). 35 However, the field of orthopaedics still lags behind other fields in the rate of increased female and minority representation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Over the past two decades, the percentage of female orthopaedic residents has risen moderately from 11.0% in 2005 to 14% in 2017 (127.3% increase). 29,35,36 Interestingly, the field of musculoskeletal oncology is more representative of female surgeons (21.1%) than the orthopaedic workforce as a whole (5.0%). 35 However, the field of orthopaedics still lags behind other fields in the rate of increased female and minority representation.…”
Section: Discussionmentioning
confidence: 99%
“…29,35,36 Interestingly, the field of musculoskeletal oncology is more representative of female surgeons (21.1%) than the orthopaedic workforce as a whole (5.0%). 35 However, the field of orthopaedics still lags behind other fields in the rate of increased female and minority representation. 29,37 Conversely, the field of orthopaedic surgery has actually seen a decline in minority representation within residency training programs since 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An article in this month’s Clinical Orthopaedics and Related Research ® [7] found that only one in 20 orthopaedic surgeons billing for patient care under Medicare is a woman. This ratio is likely similar for orthoapedic surgeons who provide care to patients who do not have Medicare insurance.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Where Do We Need To Go? Rodgers et al [7] found that despite our civilized and seemingly integrated society, there is still an overwhelming disparity in gender inclusion in orthopaedic surgery. What will it take to eliminate the barriers that hinder women from freely entering the profession?…”
mentioning
confidence: 99%